2004
DOI: 10.1021/ic049789v
|View full text |Cite
|
Sign up to set email alerts
|

The Reactions of Tellurium Tetrahalides with Triphenylphosphine under Ambient Conditions

Abstract: The reactions of tellurium tetrahalides and triphenylphosphine in tetrahydrofuran have been carried out under ambient conditions and afford [(Ph(3)PO)(2)H](2)[Te(2)X(10)] [X = Cl (1), Br (2)] and [(Ph(3)PO)(3)(OH(3)])(2)[TeI(6)] (4). The X-ray structures of 1 and 2 show that they are isostructural and contain discrete [Te(2)X(10)](2-) anions exhibiting octahedral coordination around both tellurium atoms with one shared edge and [Ph(3)POH...OPPh(3)](+) cations that show strong hydrogen bonds (the O...O distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 64 publications
2
37
0
Order By: Relevance
“…Selenium(IV) and tellurium(IV) halides are reduced by phosphines; the complex mixture of products formed depends upon the reaction conditions, but the primary reaction is the formation of halophosphorus(V) cations [PR 3 X] + and selenium or tellurium anions, sometimes along with elemental Se or Te [344][345][346]. In the presence of air and moisture, the major products with TeX 4 are protonated phosphine oxide salts of halotellurates(IV) [346].…”
Section: Group 16mentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium(IV) and tellurium(IV) halides are reduced by phosphines; the complex mixture of products formed depends upon the reaction conditions, but the primary reaction is the formation of halophosphorus(V) cations [PR 3 X] + and selenium or tellurium anions, sometimes along with elemental Se or Te [344][345][346]. In the presence of air and moisture, the major products with TeX 4 are protonated phosphine oxide salts of halotellurates(IV) [346].…”
Section: Group 16mentioning
confidence: 99%
“…In the presence of air and moisture, the major products with TeX 4 are protonated phosphine oxide salts of halotellurates(IV) [346]. Careful bromination of phosphine selenides affords [(R 3 P)SeBr 2 ] R = NMe 2 , NEt 2 , Cy, i Pr, t Bu) which have T-shaped geometries at Se (10e − systems) and are formally phosphine complexes of SeBr 2 [347,348].…”
Section: Group 16mentioning
confidence: 99%
“…During crystallization trials of (I), we observed the formation of crystals of various morphologies and colours, depending on the solvents and conditions used. This observation, and the well known facts that organotellurium(IV) iodides frequently display secondary bonding, which gives rise to a wide variety of supramolecular assemblies ), that they are often polymorphic [see, for example, McCullough et al (1985), Nä rhi et al (2004), Srivastava et al (2004) and Beckmann et al (2005), and references therein], and that they have colours that are related to the occurrence of noncovalent interactions (McCullough et al, 1985;Dewan & Silver, 1977), led us to a systematic study of these specimens.…”
Section: Commentmentioning
confidence: 98%
“…It was reported already in the early 1930s that this compound crystallizes as two different polymorphs: one form is orange red and the other deep red. 81 The crystal structures of both polymorphs were established recently 79 and show that the I· · ·I contacts in the deeper red polymorphs are shorter than in the orange -red polymorph. The packing of molecules in both polymorphs is shown in Figure 9.…”
Section: -53mentioning
confidence: 98%
“…It has been reported that there is a qualitative correlation between the lengths of the Te-I bonds in R 2 TeI 2 and the strength of the secondary bonding interactions, 79 though the bond lengths are naturally also affected by the organic group. McCullough et al 80 have correlated the secondary bonds with the color of the crystalline material.…”
Section: -53mentioning
confidence: 99%